PENGELOLAAN BAHAN UBI MENJADI STOK CEMILAN ANAK SANTRI PENGHAPAL AL QURAN DI YAYASAN LAYAR DAKWAH - Masdania Zurairah; Asmara Sari Nasution; Nabila Yudisha; Margie Subahagia; Rizkha Rida (Bajang Institute, 2023)
The Screen Da'wah Foundation in the Vocational Tahfidz Dormitory (TPA) section, carried out vocational activities. One of the activities carried out was making cassava snacks. Remembering that tahfiz children whose main task is memorizing the Koran, with this activity will add to the skills of tahfidz children later when serving after completing 30 juz memorization. It is very easy to make and the cost of manufacture is also very cheap. The results of these sweet potato chips will be data on the percentage value which students and their ustadzah prefer more. The snacks produced taste fragile/crispy, soft, spicy level 5, spicy lepel 2. The most preferred taste of cassava students who do not go through boiling where the sweet potato chips produced taste crunchy and brittle is 85%. Meanwhile, the spiciness that students like is level 5 by 70%. The comparison between the ustadzah and the students regarding the feeling of softness is 85%: 15%.